Pengaruh Sudut Pengarah Aliran Pada Turbin Air Crossflow Tingkat Dua Terhadap Putaran dan Daya - Satria Candra Laksmana; A'rasy Fahruddin; Ali Akbar (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2018)
The potential of hydro energy is very large both for large scale and for small scale. Until now, the need for energy continues to increase, so that energy is a very important element in the development of a country or a region. Cross-flow turbines are one type of turbine that is often used for PLTMH. In this study planning a cross-flow water turbine applied to the height and amount of water per second in the irrigation channel water flow, this water flow will rotate the turbine shaft to produce mechanical energy. With variations in the direction of the turbine flow direction, namely 30o, 35o, and 40o, and the same variation of water discharge 10,5 L / s, 21 L / s and 31,5 L / s to determine the effect on the rotation and the power produced. In this study with 12 turbine blades, 30o blade angle, 40o flow direction angle, and 31.5 L / s water discharge obtained the highest first stage turbine rotation value is 478 rpm. Whereas at the flow direction angle of 30o with the same water discharge which is 31.5 L / s so that the first stage of the turbine is obtained is 296 rpm.